Aqueous extract of Calamus rotang as a novel immunoadjuvant enhances both humoral and cell mediated immune response - Amit Gupta; Ajam C Shaikh; Sushama R Chaphalkar (Shahrekord University of Medical Sciences, 2017)
Introduction: Search for new adjuvants for human vaccines has become an expanding field of research in the last thirty years for generating stronger vaccines, capable of inducing protective and long lasting immunity in humans. The objective of this study was to investigate the immunoadjuvant activity of aqueous extract from the leaves of Calamus rotang using phosphate buffered saline (PBS, pH 7.2) against hepatitis B vaccine containing surface antigen (HBsAg; 20 μg/mL). Methods: In this research qualitative study was evaluated in order to determine the presence of secondary metabolites and further confirmation of these metabolites through high performance thin layer chromatography (HPTLC) and identification by liquid chromatography mass spectrometry (LC-MS). In addition, indirect Elisa was performed using HBsAg as coating antigen and this aqueous extract showed anti-HBsAg titre at higher doses as compared to standard and control. In continuation of these studies, Swiss mice were immunized subcutaneously on day 0 with HBsAg (20 μg/mL, 100 μL) and collect splenocytes on day 4 for splenocyte proliferation assay (ex vivo studies; again exposed with HBsAg) and estimation of Th1 (IFN-gamma and tumor necrosis factor [TNF-α]) cytokines from cell culture supernatant. Results: The aqueous leaves extract of C. rotang showed dose dependent enhancement in antibody titre and proliferation at higher doses (P < 0.01) with respect to HBsAg. In addition, this aqueous extract also showed improvement in Th1 (IFN-gamma and TNF alpha) cytokines at higher doses (P < 0.01) from cell culture supernatant as compared to standard HBsAg. Conclusion: Calamus rotang has additive adjuvant activity against hepatitis B vaccine antigen containing alum and may help to raise antibodies against HBsAg under challenging administration regimen and might be a potent vaccine adjuvant.